THE EFFECT OF MAGNETIC FIELD EXPOSURE ON MEDIUM TO PROTEASE PRODUCTION BY Bacillus sp. - Sumardi, Sumardi; Agustrina, Rochmah; Irawan, Bambang; Pratiwi, Ajeng (BIOVALENTIA: Biological Research Journal, 2018)
This research was purposed to understand the effect of 0.2mT magnetic field exposure treatment for 10 minutes toward medium components to the production of protease in Bacillus sp. That magnetic field exposure treatment was given to 8 medium components namely Milk, Yeast, NaCl, KH2PO4, MgSO4, (NH4)2SO4,Agar and Aquadest. Data from Qualitative Proteolytic Activity test on Bacillus sp. indicated that in all treatment, the bacteria were able to produce the enzyme. The highest Proteolytic Index (IP) from all those treatments came from the magnetically exposed KH2PO4 which was 7.17 at the 10th incubation hour. Treatment of exposure to magnetic fields is also given to the liquid medium. Quantitative data of enzyme activity showed that the best incubation time of protease production by Bacillus sp. is the 24th incubation hours with result of 0.031 U/ml. Exposure of 0.2 mT magnetic field for 10 minutes to the NaCl component in Mendel's fluid medium yielded the highest protease activity of 0.067 U/ml.